(untitled) (Konferensiyalar | Conferences, 2024)
This article discusses the issues of innovative technologies in education, namely digital divide, effectiveness and learning outcomes, engagement or destruction. Furthermore, technology should not replace traditional teaching methods as the important use of technology in a smart way that helps intercultural competence and provide students with necessary skills to succeed in divers and technology-driven society. The goal of the research is clarify information the advantages and disadvantages of using modern devices in education and classical methods.